Right procedure, wrong organ, an unusual case report of aortic trauma in a multiple injured patient. - Mitsos, A; Chantler, J; Konstantinou, E; Fotis, T; Lambrinou, E; Uberoi, R; Stacey, R; Byrne, J (2009)
Blunt traumatic injury and acute dissection of thoracic aorta is increasing in incidence in seriously multi-trauma patients, remaining highly lethal. Early identification and repair is the key to a successful outcome. We report an unusual case of a 62-year-old man involved in a motor vehicle accident after subarachnoid hemorrhage due to an intracranial artery aneurysm rupture. The post-traumatic aorta dissection was overlooked during the initial evaluation and was found incidentally later during an attempt for endovascular treatment of the intracranial aneurysm. The pitfalls in the diagnostic approach of this patient are discussed and the paramount importance of the correct interpretation of all the available clinical and investigational findings in multiple injured patients are highlighted.